Energy production in the 800m - Arcelli, E.; Bianchi, A.; Tebaldini, J.; Bonato, M.; La Torre, A. (New Studies in Athletics, 2012)
Understanding the aerobic and anaerobic energy mechanisms in the 800m can have important practical consequences for coaches trying to correctly plan and manage an athlete's training. This knowledge is especially useful now that low cost, easy to use equipment is available for measuring blood lactate concentration after a competition or in training. The purpose of this study was to examine the contribution of the anaerobic lactate mechanism from the point of view of the total energy expenditure and energy expenditure at different stages of the 800m. Blood lactate concentration was measured in 18 male athletes at the end of a race and after time trials of 300m and 600m run at the same pace as the race. The data confirm earlier findings that blood lactate concentration at the end of the 800m tends to decrease with the increase of the time of the race. It was also found that the contribution of the anaerobic lactate mechanism peaks from the start to 300m, falls between 300m and 600m and is at its minimum at the end of an 800m race. Conclusions include general advice for working with athletes with typical strength-weakness profiles for the two mechanisms studied.